Advances in Affective and Pleasurable Design Proceedings of the AHFE 2018 International Conference on Affective and Pleasurable Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Fukuda, Shuichi (Advances in Intelligent Systems and Computing, 2019)
This book discusses the latest advances in affective and pleasurable design. Further, it reports on important theoretical and practical issues, covering a wealth of topics including aesthetics in product and system design, design-driven innovation, affective computing, evaluation tools for emotion, Kansei engineering for products and services, and many more. Based on the AHFE 2018 International Conference on Affective and Pleasurable Design, held on July 21-25, 2018, in Orlando, Florida, USA, the book provides a timely survey and inspiring guide for all researchers and professionals involved in design, e.g. industrial designers, emotion designers, ethnographers, human-computer interaction researchers, human factors engineers, interaction designers, mobile product designers, and vehicle system designers. .